The Identity of Father and Daughter in Aftersun Movie Through Collective and Individual Memory - Nabila Pipin Pinasti; Salsyabila Eka Putri; Euis Meinawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Film functions as a medium through which memory and identity are constructed, particularly in the context of family relationships. The present study draws upon Maurice Halbwachs' theory of collective and individual memory to analyze the father-daughter relationship depicted in the film Aftersun. A plethora of studies have previously examined the nexus of memory and identity in cinematic works. However, research that explores the intricate interplay between collective and individual memory within the context of intimate family relationships remains under-explored. The present study aims to analyze how Calum and Sophie's shared experiences shape their emotional closeness, as well as how Sophie, as an adult, reinterprets her childhood memories to reconstruct her understanding of herself and her father. The data were collected through repeated viewings, dialogue transcription, and selection of relevant scenes, employing qualitative descriptive methods. The findings indicate that collective memory, manifested through shared activities and dialogues, fosters cohesion and relational identity. Conversely, unshared individual memories influence Calum's role as a father. In adulthood, Sophie engages in a process of self-reflection and identity reconstruction, working through her memories of childhood to reinterpret her shared identity with her father.